A study on contemporary legal issues regarding the division of harta sepencarian in Malaysia / Mohd Rafiezi Mohd Tahir, Nurul Qistini Qamarul Abrar and Nur Edwina Mohd Zaidi - Mohd Tahir, Mohd Rafiezi; Qamarul Abrar, Nurul Qistini; Mohd Zaidi, Nur Edwina (2008)
This project paper surrounds the discussion on the division of harta sepencarian during the dissolution of marriage, in which it is focused specifically the issue of Employees' Provident Fund (EPF) and the current scenario in Syariah courts which may contribute to the increasing number of the claims on harta sepencarian. Harta sepencarian is legally recognized by our local law through Islamic Family Law Enactments. The courts have their own discretion to determine the portion of the property to be divided between the spouse according to the circumstances and requirements given by law. The discussion will elaborate more on the types of the property and the contributions of each party that will entitle them the property. Besides having discussions on statutory requirements, many cases will be referred so as to get a clear picture on how the application of the division will be effected. The main objective of conducting this research is to find out the positions on claims made on EPF money. This is a new scenario happens nowadays and legal solutions must be provided for the next generation. Secondly, there are complaints and reports made by the wife that the procedures for accomplishing an application for harta sepencarian is very lengthy and it is a waste of time when they have to wait for longer period just to settle the claims. On the other hand, the lack of understanding among Muslims is one of the factors for the backlog cases. Any other factors will be recognized and suggestions will be tendered. The research aims to tender any relevant recommendations and suggestions for the betterment of our system. We have to be in line with current changes and situations so that we will not be left behind.